Factors Affecting Adherence to Antihypertensive Medication: Systematic Review - Arif Imam Hidayat; Galih Noor Alivian; Sidik Awaludin; Iwan Purnawan; Lita Heni Kusumawardani; Wahyudi Mulyaningrat (International Journal of Biomedical Nursing Review, 2023)
Introduction: Hypertension is one of the most common cardiovascular diseases around the world. Hypertension influence so many aspect in patient’s live, not only physically but psychologically as well. Identifying and understanding factors related with treatment adherence in patient with hypertension can be very important to develop specific strategies to increase patient’s quality of life, prevent complications, and reduce re-hospitalization rate in patient with hypertension. Objective: This paper reviewed and synthesized the previous studies of factors related with treatment adherence in patient with hypertension. Method: Literature study in 15 journals through Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Ovid, Taylor and Francis, and Science Direct, and manual searching from the reference list of previous obtained using keywords definition of treatment adherence, dimension of treatment adherence in patient with hypertension, and factors related with treatment adherence in patient with hypertension. Data were analyzed in tables contain title, author, year, methodology, result, and recommendation. Result: Patient adherence to treatment can be describe as an extent of patient’s behavior to follow the medication, diet, and lifestyle changes as recommended by the healthcare provider. Treatment adherence represents patient’s behavior after discussion between patient and healthcare provider. Patient have right to agree or refuse the treatment after get enough information from healthcare provider. Conclusion: The individualized approach can be very useful to assess and understand the cause of patient non-adherence with treatment hypertension. In the future this information can be useful to decide nursing theory that fit to underpinning the intervention and also can be used to plan intervention to increase treatment adherence of patient with hypertension.